The diagnostics and management of acute diverticulitis: a systematic review of the literature - Kildušis, Edvinas; Jasponytė, Ieva; Brimas, Gintautas (Lietuvos chirurgija, 2024)
Background. To examine the latest guidelines for the diagnostics and treatment of acute diverticulitis and to formulate recommendations for the diagnostics and management of acute diverticulitis based on them. Research material and methods. A selection of the latest guidelines for the diagnostics and treatment of acute diverticulitis in the PubMed medical database in English and German, during 2012–2024 period, was performed based on the requirements criteria of the PRISMA literature review and the PICO data selection method. Key words used in the search: “acute”, “diverticulitis”, “guidelines”, “diverticulosis”, “diagnostics”, “treatment”. Results. Although different guidelines disagree on the order of UG and CT with intravenous contrast, 6/6 guidelines agree on UG and 7/7 on the appropriateness of CT with contrast in the diagnostics of acute diverticulitis. 7/8 guidelines agree that routine antibiotic therapy is unwarranted in the treatment of uncomplicated diverticulitis. 6/6 guideline authors agree on the treatment of small abscesses with antibiotic therapy, and 7/7 on the treatment of large abscesses with antibiotic therapy and drainage. 5/7 guidelines support Hinchey III antibiotic therapy and primary anastomosis treatment with/without preventive ileostomy. Hinchey IV recommendations for tactics in the treatment of acute diverticulitis are distinguished. Planned surgery after a complicated episode of diverticulitis is routinely recommended by 3/7 guidelines, 2/7 guidelines – when strictures or fistulas are formed, 2/7 – the decision should be made based on the patient’s condition. Most guidelines do not recommend conservative secondary prophylaxis after an acute episode of diverticulitis. Conclusions. UG and CT with intravenous contrast are the methods of first choice for the diagnostics of acute diverticulitis. In case of uncomplicated diverticulitis, routine antibiotic therapy is not recommended, drainage is used only for large abscesses, and antibiotics for both small and large abscesses. Primary anastomosis with/without preventive ileostomy is preferred for Hinchey III acute diverticulitis. Recommendations for the treatment tactics of Hinchey stage IV AD differ in the literature.